Hybrid contractual landscapes of governance: Generation of fragmented regimes of public accountability through urban regeneration. (March 2021) - Taşan-Kok, Tuna; Atkinson, Rob; Martins, Maria Lucia Refinetti
In this article we explore the idea of public accountability in the contemporary entrepreneurial governance of cities, which are influenced by market dependency and private sector involvement. We specifically focus on the fragmentation of public accountability through hybrid contractual landscapes of governance, in which the public and private sector actors interactively produce a diversity of instruments to ensure performance in service. This is in sharp contrast to the traditional vague norms and values appealed to by urban planning institutions, to safeguard the public interest. We argue that within these complex contractual governance environments public accountability is produced by public and private sector actors, through highly diverse sets of contractual relations and diverse control instruments that define responsibilities of diverse actors who are involved in a project within a market-dependent planning and policy making environment, which contains context-specific characteristics set by the specific rules of public-private collaboration. These complexities mean public accountability has become fragmented and largely reduced to performance control. Moreover, our understanding of contractual urban governance remains vague and unclear due to very limited empirical studies focusing on the actual technologies of contractual urban development. By deciphering the complex hybrid landscapes of contractual governance, with comparative empirical evidence from The Netherlands, UK and Brazil, we demonstrate how public accountability is assuming a more 'contractual' and unpredictable meaning in policy and plan implementation process.